The Dictionary of substances and their effects - Gangolli, S. (Royal Society of Chemistry, 2005)
This 2005 electronic version of the original seven-volume collection of vital information has been updated to contain approximately 5,300 chemicals and their impact on the environment. Detailed information about the toxicity of the chemicals, physical properties and regulatory requirements is also presented. The information can be accessed through a live summary table that links to the detailed summaries or by browsing the table of contents for a specific chemical.